Two-level variational chirp component decomposition for capturing intrinsic frequency modulation modes of planetary gearboxes. (1st September 2022) - Wei, Sha; He, Qingbo; Wang, Dong; Peng, Zhike
Abstract: Due to the advantages of high transmission ratios and large carrying capacity, planetary gearboxes have been widely used in various industrial machinery. Vibration signals caused by planetary gearbox faults usually have intrinsic frequency modulation (FM) modes. Since the intrinsic FM modes have fast time-varying and oscillating characteristics, extraction of the intrinsic FM modes is still a challenging task. In this paper, a two-level variational chirp component decomposition (VCCD) approach is proposed to capture the intrinsic FM modes from vibration signals caused by planetary gearbox faults. Specifically, to avoid complicated sideband analysis, Level 1 of the VCCD is designed to extract gear fault characteristics from an amplitude modulation (AM) signal obtained by the Hilbert transform and a preliminary fault detection conclusion can be drawn to locate gear faults. Level 2 of the VCCD is employed to accurately extract the oscillation FM mode of a FM signal obtained by removing the AM signal from an original vibration signal. Results of Level 2 of the VCCD can not only verify the initial conclusion previously drawn from Level 1 but also explicitly and comprehensively reveal fault features of planetary gearboxes. The potential and effectiveness of the proposed two-level VCCD method are verified by two simulated cases related to planet gear faults under variable speed conditions and two experiments respectively related to a broken ring gear under constant speed conditions and a worn sun gear under variable speed conditions.